Knowledge, Attitude and Practice Toward COVID-19: A Cross-Sectional Study of Staff in China-Guinea Friendship Hospital, Guinea - Ji, Wenyan; Camara, M'Bemba Abdoulaye; Xia, Jinggang; Ma, Xiaobo; Chen, Xintong; Liu, Ying (Frontiers in Public Health, 2022)
Background The purpose of this study was to assess the level of knowledge, attitude and practice of COVID-19 among staff in China-Guinea Friendship Hospital, and to confirm the effect of nosocomial infection management. Methods This cross-sectional study was conducted in December 2021. Information on socio demographic data, knowledge, attitude and practices related to COVID-19 was collected through a self-administered questionnaire. Results A total of 143 employees participated in the survey, with a response rate of 99.31% and a vaccination rate of 95.10%. The average knowledge score of COVID-19 was 8.39 ± 1.3 points (10 points in total), without significant differences between subgroups with different demographic variables (P > 0.05); more than 80% of the participants had a positive attitude, and 72.03–93.01% of the participants could take appropriate preventive practices in different environments such as hospital, outdoor or home. Conclusion The staff of the China-Guinea Friendship Hospital has good knowledge of COVID-19, a positive attitude and appropriate preventive practices. It can be concluded that the current nosocomial infection management is active and effective. Therefore, this study suggests that comprehensive activities such as training, promotion and supervision of COVID-19-related knowledge and countermeasures should be widely and continuously implemented in healthcare facilities, which will continuously improve the overall KAP level of hospital staff and play an important role in curbing the COVID-19 pandemic.